2013
DOI: 10.3382/ps.2012-03001
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of white striping under commercial conditions and its impact on breast meat quality in broiler chickens

Abstract: The aims of this study were to evaluate the incidence of white striping (WS) under commercial conditions and assess its effect on some quality traits in broiler breast fillets. In the first experiment, occurrence of WS (absence = normal; presence classified in 2 levels as moderate or severe) was assessed in a major commercial processing plant on 28,000 breast fillets (pectoralis major muscles) chosen at random from 56 flocks of broilers processed at 45 to 54 d of age. In the second experiment, 153 fillets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
148
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 18 publications
22
148
3
8
Order By: Relevance
“…The impact of WS defect should not be underestimated because a recent survey estimated that current incidence rate under commercial production was around 12.0% (8.9 and 3.1% in moderate and severe degree, respectively) (Petracci et al, 2013b). At present, while fillets showing severe WS are usually downgraded by processors and used for manufacturing further processed products (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of WS defect should not be underestimated because a recent survey estimated that current incidence rate under commercial production was around 12.0% (8.9 and 3.1% in moderate and severe degree, respectively) (Petracci et al, 2013b). At present, while fillets showing severe WS are usually downgraded by processors and used for manufacturing further processed products (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…White striping is a new quality issue described by the appearance of white striation parallel to muscle fiber on the surface of Pectoralis major muscles (Petracci and Cavani, 2012). A recent survey has estimated that incidence of white-striped breast fillets was around 12% (Petracci et al, 2013b). The causes of WS are still unknown and no sign of systemic infections was found, but the histological evaluations showed that WS usually coupled with muscle degeneration and myopathic changes beneath the striation area (Kuttappan et al, 2013a;Petracci et al, 2013c;Sihvo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…White-striped fillets are characterised by the appearance of white striations parallel to muscle fibres on the surface of the Pectoralis major muscle (Kuttappan et al, 2009). Approximately 3% of medium-sized birds (average live weight 2.75 kg) from standard and highbreast yield genotypes raised under commercial conditions in Italy are affected by severe white striping (Petracci et al, 2013a). Recently, it has also been observed that whitestriped meat can be accompanied by another type of muscle abnormality called 'wooden breast', which is characterised by macroscopically visible hard, bulging and pale area in the caudal part of the fillet (Sihvo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Meat quality defects, which have been linked to selection on growth rate and breast muscle development in chickens, are, for instance, the pale, soft, exudative (PSE)-like and dark, firm, dry (DFD)-like meat conditions, white striping of breast meat, and "wooden" breast condition (Petracci et al, 2009;Kuttappan et al, 2012;Petracci et al, 2013;Kralik et al, 2014;Mudalal et al, 2015). These quality aberrations are associated with altered functional properties of meat, which, depending on the respective defect, can affect pH, color, water-holding capacity, and tenderness of raw and/or cooked meat (Woelfel et al, 2002;Wilhelm et al, 2010;Petracci et al, 2013;Mudalal et al, 2015). However, it was also suggested that, although intense selection on growth performance and breast yield elicited differences in muscle tissue histology and metabolism, there is little evidence of adverse effects on meat quality in chickens besides slight modifications in color (Rémignon and Le Bihan Duval, 2003;Duclos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%